Phylogeny and affiliation of European Anthomyzidae (Diptera) based on mitochondrial 12S and 16S rRNA - Roháček, Jindřich; Tóthová, Andrea; Vaňhara, Jaromír (Zootaxa, 2009)
The phylogenetic Bayesian analysis of combined mitochondrial 12S and 16S rRNA gene markers in European representatives of Anthomyzidae supported the monophyly of the family, confirmed the validity of the genera and provided a resolution of the generic affiliation of some aberrant species. The interrelationships of most genera have not been resolved definitively due to insufficient posterior probability values. Despite this, the clade clustering the genus Anthomyza Fallén, 1810, Fungomyza Roháček, 1999 and the Anthomyza socculata group is considered to reflect the real phylogenetic relationships of these taxa as it is also supported by morphological data. The relationships within the genus Anthomyza are resolved and monophyly of its species-groups confirmed. Within the genus Stiphrosoma Czerny, 1928, S. fissum Roháček, 1996, a species of unknown relationships, was found to be most closely allied to S. sabulosum (Haliday, 1837). Based on the above analysis a removal of the aberrant species Paranthomyza caricis Roháček, 1999 and Anthomyza socculata (Zetterstedt, 1847) from genera to which they were formerly affiliated, is suggested.